UJI IN-SILICO SENYAWA TURUNAN KURKUMINOID SEBAGAI INHIBITOR BRUTON TYROSINE KINASE PADA LEUKIMIA LIMFOSITIK KRONIS - Abdul Mulki Irpani; Muhamad Ilham Bintang; Al-fira Putriyanti; Deistha Adinda; Jajang Japar Sodik (LPPM Universitas Bakti Tunas Husada, 2025)
Leukemia is a blood cancer that occurs due to abnormal blood cell growth, especially white blood cells in the bone marrow. Research shows that curcumin is proven to be effective in inhibiting the activity of the NF-κB transcription factor which is often involved in the proliferation of cancer cells. This study aims to determine the potential of natural curcuminoid compounds against specific blood cancers, namely chronic lymphocytic leukemia. Through in-silico testing of curcuminoid derivative compounds against the Bruton Tyrosine Kinase protein target which plays a role in the pathophysiological process of chronic lymphocytic leukemia. The results of docking the test ligand molecule on the Tyrosine-protein kinase BTK enzyme, the native ligand has the lowest binding energy value (ΔG) of -12.04 kcal/mol with an inhibition constant (KI) of 1.49 nM. As a comparison drug, imatinib showed ΔG -11.05 kcal/mol with a KI of 7.88 nM. Test ligands s02, s05, and s08. Ligand s02 showed a ΔG of -9.43 kcal/mol with a KI of 123.19 nM, while s05 had a ΔG of -9.09 kcal/mol with a KI of 218.10 nM. Meanwhile, s08 recorded a ΔG of -9.33 kcal/mol and a KI of 143.83 nM. Although the affinity values of the three test ligands were lower than those of the natural ligands, they had the potential to bind to the target enzyme. Based on the interaction analysis, it was seen that s05 had the potential for competitive inhibition, while s02 and s08 showed lower interaction stability compared to imatinib. This indicates that s05 has the greatest potential as a potential inhibitor of the BTK enzyme compared to other test ligands.